Dynamic deformation, damage and fracture in composite materials and structures - Silberschmidt, Vadim V. (Woodhead Publishing series in composites science and engineering, 2022)
Dynamic Deformation, Damage and Fracture in Composite Materials and Structures, Second Edition reviews various aspects of dynamic deformation, damage and fracture, mostly in composite laminates and sandwich structures, and in a broad range of application areas including aerospace, automotive, defense and sports engineering. This book examines low- and high-velocity loading and assesses shock, blast and penetrative events, and has been updated to cover important new developments such as the use of additive manufacturing to produce composites, including fiber-reinforced ones. New microstructural, experimental, theoretical, and numerical studies with advanced tools are included as well. The book also features four new chapters covering topics such as dynamic delamination, dynamic deformation and fracture in 3D-printed composites, ballistic impacts with fragmenting projectiles, and the effect of multiple impacting.